Emulsion liquid membrane pertraction of Cr (III) from aqueous solutions using PC-88A as carrier - Garcia, Maria Guadalupe (2013)
Liquid membrane processes have emerged as alternative techniques to conventional processes for concentration and separation of metal ions from aqueous effluents. The removal of chromium(III) from synthetic aqueous solutions by an emulsion liquid membrane technique (ELM) was investigated. 2-Ethylhexyl phosphonic acid mono-2-ethylhexyl ester (PC-88A) was used as carrier, Span 80 as surfactant, light paraffin as additive, and ammonium persulfate [(NH4)2S2O8] as stripping agent. Different physical and chemical parameters such us stirring speed, metal ion concentration and pH of the continuous phase, carrier concentration, organic/aqueous stripping ratio (O/S), and internal stripping agent concentration have been analyzed. The results demonstrated that working in a batch mode at the optimum ELM extraction–stripping condition 94% of chromium(III) was removed during the first 5 min of operational time. The ELM showed high stability up to 30 min. Different interfacial reactions involving the chromium complexes and the facilitated transport of Cr(III) through the ELM were proposed.